PENTINGNYA PENDIDIKAN AGAMA KRISTEN BAGI KELUARGA KRISTEN DALAM KITAB “ ULANGAN 6:1-9” GPIA KASIH SURGAWI JEMBER - Elmika Yulianti Br Pandia (Metanoia, 2022)
Introduction which contains the Background of the Problem, Identification of the Problem, Focus of the Problem, Formulation of the Problem, Benefits of Research Results, Research Assumptions, Definition of Terms, and Writing System. Literature study that contains about, Christian Religious Education, the understanding of Religion, the understanding of Education, Christian Religious Education, Factors affecting Children's Religious Education, Education, Christian Religious Education to Children, Importance of Christianity. Qualitative research methods that contain models and types of research methods, interview research subjects, interview research information, research implementation, data collection techniques, data analysis techniques, organizing data, and data creatiability. Research and discussion results that contain descriptions of research sources, description of research results, discussion and testing of data.